Myelin Recovery in Multiple Sclerosis: The Challenge of Remyelination - Edward L. Hogan; Ewa Kurowska; Naren L. Banik; Maria Podbielska (Brain Sciences, 2013)
Multiple sclerosis (MS) is the most common demyelinating and an autoimmune disease of the central nervous system characterized by immune-mediated myelin and axonal damage, and chronic axonal loss attributable to the absence of myelin sheaths. T cell subsets (Th1, Th2, Th17, CD8+, NKT, CD4+CD25+ T regulatory cells) and B cells are involved in this disorder, thus new MS therapies seek damage prevention by resetting multiple components of the immune system. The currently approved therapies are immunoregulatory and reduce the number and rate of lesion formation but are only partially effective. This review summarizes current understanding of the processes at issue: myelination, demyelination and remyelination—with emphasis upon myelin composition/ architecture and oligodendrocyte maturation and differentiation. The translational options target oligodendrocyte protection and myelin repair in animal models and assess their relevance in human. Remyelination may be enhanced by signals that promote myelin formation and repair. The crucial question of why remyelination fails is approached is several ways by examining the role in remyelination of available MS medications and avenues being actively pursued to promote remyelination including: (i) cytokine-based immune-intervention (targeting calpain inhibition), (ii) antigen-based immunomodulation (targeting glycolipid-reactive iNKT cells and sphingoid mediated inflammation) and (iii) recombinant monoclonal antibodies-induced remyelination.